Analysis of roughness performance of chloride-stabilised rural roads. Issue 13 (10th November 2021) - Osorio-Lird, Alelí; Chamorro, Alondra; González, Álvaro
ABSTRACT: Rural roads play a crucial role in the economic and social development of societies. Therefore, they should be managed accordingly and supported by consistent public policies and suitable management practices. Maintenance requirements and costs depend upon the desired serviceability expected for the prevailing traffic, which can be estimated from the road roughness. Given the increasing use of chloride stabilisers to improve the service level of rural roads, it is crucial to objectively assess the performance of these roads over time to perform life-cycle cost analyses for effective management. The objective of this study was to assess the roughness of chloride-stabilised rural roads over time and to propose a performance model from the analysis. As a result, a model for roughness prediction of chloride-stabilised roads was developed and successfully validated, considering an exponential estimation curve based on the age of the road. The proposed model is statistically significant, considering a 95% confidence level range of IRI predicted ± 0, 88 m/km. This result indicates that age provides confident information about the IRI. This model is proposed for network-level management of rural roads in terms of IRI.